Malignant Pleural Mesothelioma - Boltz, Kathy (MD Conference Express, 2015)
New approaches to malignant pleural mesothelioma are developing through increased knowledge of its genomic landscape that has informed treatment approaches through precision medicine. This session also discussed the roles of surgery and radiotherapy for mesothelioma.